Improving Nitrogen Use Efficiency in Aerobic Rice Based on Insights Into the Ecophysiology of Archaeal and Bacterial Ammonia Oxidizers - Farooq, Muhammad Shahbaz; Uzair, Muhammad; Maqbool, Zubaira; Fiaz, Sajid; Yousuf, Muhammad; Yang, Seung Hwan; Khan, Muhammad Ramzan (Frontiers in Plant Science, 2022)
The community abundance and structural composition of nitrogen (N) transformation-related microbes with certain environmental requirements render information about the N-cycle. The aim of this review was to explore the major challenge of low N-use efficiency and N-dynamics in aerobic rice and to reveal the agronomic-adjustive measures to increase N-use efficiency through insights into ecophysiology of ammonia oxidizers. Water-saving practices like alternate wetting and drying (AWD) has been evaluated in lowland rice, however, few studies have been conducted on N-dynamics in aerobic rice. Biological ammonia-oxidation is majorly conducted by two types of microorganisms, ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB). This review focuses on how diversified are the ammonia-oxidizers, which factors affect their activities and abundance under varying soil conditions. It summarizes the findings on pathways of N-cycle, rationalize recent research about ammonia-oxidizers in N-cycle and thereby suggests the adjustive-agronomic measures to reduce N-losses. This review suggests that varying soil properties significantly impact the structural composition and abundance of ammonia-oxidizers. Nitrification-inhibitor (NI) especially Nitrapyrin reduces the nitrification-rate and inhibit the abundance of bacterial-amoA without impacting archaeal-amoA. In contrast, some NIs confine the hydrolysis of synthetic-N and therefore keep low NH4+-N concentrations which exhibit no or very slight impact on ammonia-oxidizers. Variation in soil properties, instead of applying synthetic N-fertilizer and NIs influence more the structure and abundance of ammonia-oxidizers. Mixed application of synthetic and organic N-fertilizers enhances the N-use efficiency and plant N-uptake by reducing ammonia-N losses. High salt concentration boosts the community abundance while limiting the diversity of AOB and vice versa for AOA, whereas AOA has lower rate for potential-nitrification than AOB and denitrification accounts for higher N2 production. Archaeal abundance, diversity, and structural composition change along an elevation gradient and increase with increased accumulated soil saturation, NH4+ and organic matter which imply these as water critical factors for AOA. Abundance analysis revealed that structural composition of AOA was not highly responsive to the changes in soil conditions or N-amendment. Further studies are suggested using cultivation-based controlled-experiments for better understanding of AOA and AOB mechanisms to environmental variabilities to evaluate conditions which allow ammonia-oxidizers better-utilization of metabolic functions.